Gentiles in the novel "Blonzende Shteren" by Sholem Aleichem: "goyim" portrayed - Galiano Guzmán, José Luis (Miscelánea de Estudios Árabes y Hebraicos. Sección Hebreo, 2018)
The Yiddish author Sholem Aleichem, pseudonym of Sholem Rabinovitz, experienced the emigration from tzarist Russia to the United States due to the pressure on the Jewish population at the beginning of the 20th century. His novels reflect the lives of Eastern European Jews between two worlds: the declining Yiddish culture and the hope of the New World that took them in. In Blonzende Shteren, Sholem Aleichem portrays the attitudes and images the Jews had towards the Gentiles. He also shows the tension felt by the Jews trying to preserve their identity while coping with the need of cultural assimilation. This article analyses these images and tensions as they appear through the characters’ voices, the narrator and the author’s pseudonym. Finally, the paper aims to clarify if the literary image of Gentiles in the novel and the author’s opinion coincide.